STUDI PENGARUH SUHU DAN TEKANAN UDARA TERHADAP OPERASI PENERBANGAN DI BANDARA INTERNASIONAL KUALANAMU - I. J. A. Saragih; B. W. Yonas; N. Rinaldy (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Kualanamu International Airport (KNIA), operated since 2013, is a new airport, which supports the commercial aviation to replace the Polonia Airport. As the new airport, it is necessary to study the effect of weather on the smooth operation of flights on the Kuala Namu Airport, among others, is the element of surface temperature and air pressure (QFE). Using multiple linear regression, it can be determined the correlation of temperature and air pressure to the airplane lift force (lift). Temperature and air pressure are also used in the calculation of the height of the air density (density height). The result showed that the temperature and air pressure together have a very strong effect on the lift in every month throughout the year. The decrease in air temperature and or increase of air pressure is directly proportional to the rise of lift. The air temperature has the strongest effect in April (92.93%) and the weakest in March (84.82%). The air pressure has the strongest effect in September (24.80%) and the weakest in February (08,76%). The result of the calculation using the formula density height found that in 2015 the highest density height in June (1756.34ft) and the lowest in January (1469.11 feet). While in 2016, the density height has the highest value in March (1806.32ft and the lowest in February (1513.23ft).Keywords: air temperature, air pressure, lift, density height